Correlation Between NT pro-BNP, Troponin I and Inhospital Mortality in Miokard Akut Patients Who Have Already Undergone Percutaneous Coronary Intervention: a Report from ONE ACS Registry Subarea dr. Saiful Anwar Malang Hospital - Diah Ivana Sari; Setyasih Anjarwani; Ardian Rizal; Mohammad Saifur Rohman; Indra Prasetya (Universitas Brawijaya, 2023)
Introduction. Many research have looked into the potential of various biomarkers as predictors of intrahospital mortality in patients with STEMI. Patients with a history of heart failure, patients with STEMI with cardiogenic shock, and patients with heart failure all had a similar association between pro-BNP NT and intra-hospital mortality. In STEMI patients, troponin is another biomarker that can be utilized to predict intrahospital mortality with NT pro BNP.Objective. This study looked into the correlation between NT pro BNP and troponin I and intrahospital mortality in STEMI patients who had had PCI at RSUD dr. Saiful Anwar Malang.Material and Methods. A retrospective cohort research with an observational analysis design, targeted 391 STEMI patients who underwent PCI at RSUD dr. Saiful Anwar Malang between January 2018 and August 2022.Result. With AUC NT pro BNP 0.840 (95% confidence interval [CI]: 0.789 – 0.892) and troponin I AUC 0.818 (95% CI: 0.753 – 0.882), the ROC curve demonstrated a high degree of discriminating. The NT pro BNP 4390 cutoff value was also derived from the ROC analysis with a sensitivity of 0.882 and a specificity of 0.882. The threshold for troponin I was 7.9, with a sensitivity of 0.725 and a specificity of 0.80. From the examination of the connection, it was determined that there was a high link between NT pro BNP and intrahospital mortality in AMI EST patients who had had PCI, with a R value of 0.70; OR 10,484 (95% confidence interval [CI]: 7,731–19,366). With a R value of 0.4, there was a moderate connection between troponin I and intrahospital mortality in STEMI patients who had had PCI; the odds ratio was 6,167 (95% confidence interval: 2,286–16,637).Conclusion. There were a strong and moderate correlation between NT pro BNP and troponin I, respectively, with inhospital mortality in STEMI patient.